1985
DOI: 10.1021/ic00215a025
|View full text |Cite
|
Sign up to set email alerts
|

Diastereotopic exchange in the square-planar platinum(II) complex, (N,N'-dimethylethylenediamine)bis(guanosine)platinum(II)

Abstract: C6H5)3P]2CuBr, 47814-88-0; (dppe)CuI, 15228-76-9. ( 5 5 ) Brint, P.; Spalding, T. R. Inorg. Nucl. Chem. Lett. 1979, 15, 355. A total of six diastereomeric configurations of the chiral square-planar platinum( 11) complex (N,N'-dimethy1ethylenediamine)-bis(guanosine)platinum(II), [Pt(N,N'-Me,en)(Ci~o),]~+, are detected. Three sets of stereoisomers result from the configuration of the two coordinated ethylenediamine nitrogens, and these are designated RR, SS, and SR. In addition, the ribose moieties of the guanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 3 publications
0
68
0
Order By: Relevance
“…For a head-to-tail (HT) orientation of two guanine units, the D or L chirality is defined according to the handedness of two straight lines, one perpendicular to the coordination plane and passing through platinum and the other connecting the O6 atoms of the two guanines. [50,51] www.chemeurj.org be able to crystallize this elusive conformer by choosing those circumstances known from our work to lead to greater stability of the LHT conformer. For this, we selected the 2 ] complex (Me 4 DAE = N,N,N',N'-tetramethyl-1,2-diaminoethane).…”
Section: Introductionmentioning
confidence: 99%
“…For a head-to-tail (HT) orientation of two guanine units, the D or L chirality is defined according to the handedness of two straight lines, one perpendicular to the coordination plane and passing through platinum and the other connecting the O6 atoms of the two guanines. [50,51] www.chemeurj.org be able to crystallize this elusive conformer by choosing those circumstances known from our work to lead to greater stability of the LHT conformer. For this, we selected the 2 ] complex (Me 4 DAE = N,N,N',N'-tetramethyl-1,2-diaminoethane).…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] HT conformers have a head-to-tail orientation of the guanine bases and can have either a D or L chirality depending upon the handedness of two straight lines; one passes through the platinum center perpendicularly to the coordination plane, and the other connects the O6 atoms of the two guanines. [16,17] Furthermore, studies with the related [Pt{(S,R,R,S)-bip}G 2 ] and [Pt{(R,S,S,R)-bip}G 2 ] complexes (BIP = 2,2'-bipiperidine) indicated that a mixture of 25 % DHT, 50 % HH, and 25 % LHT essentially had a CD spectrum that lacked any intensity. However, with time, as the HT form became dominant, the intensity of the spectrum increased.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] In principle 1,10-phenanthroline (phen) and, even better, 2,9-Me 2 -1,10-phenanthroline (Me 2 phen, neocuproine) could be used to introduce steric bulk in the coordination plane ( Figure 1). 1,10-Phenanthrolines, differently from other chelating diamines, have a very rigid structure and the lone pairs on the nitrogen atoms are convergent and hence ideally oriented for complexation to a metal centre.…”
Section: Introductionmentioning
confidence: 99%